Antimicrobial potential of essential oils against antibiotic-resistant, enterotoxin-producing, and biofilm-forming Staphylococcus aureus - Munive Núñez, Karen Vanesa (2023)
Staphylococcus aureus is a major cause of subclinical mastitis in dairy cows, and the development of antibiotic resistance has limited effective treatment options. This comprehensive study evaluated the virulence, antimicrobial resistance, and therapeutic alternatives based on essential oils (EOs) for spa type t605 S. aureus isolates from subclinical bovine mastitis in São Paulo, Brazil. The study also aimed to investigate the presence of virulence genes, identify genetic variations through spa and agr typing, determine phenotypic antibiotic resistance profiles, identify major chemical constituents of eight different EOs (Citrus aurantium bergamia - Bergamot, Copaifera reticulata - Copaiba, Foeniculum vulgare - Fennel, Zingiber officinale - Ginger, Ocimum basilicum - Basil, Luma chequeen – Arrayan, Mentha spicata - Spearmint, and Eugenia caryophyllus – Clove), and assess their antimicrobial activity and cytotoxicity. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) against S. aureus isolates inoculated to 10³ CFU.mL⁻¹ and 10⁷ CFU.mL⁻¹ concentrations were also performed. Gas chromatography coupled to a mass selective detector (GC/MSD) analyzed the chemical compositions of EOs. The synergistic or antagonistic effects of selected EOs were also investigated. Cytotoxicity was assessed using the MTT assay on Vero cells. A total of 57 S. aureus isolates were screened for 49 genes. S. aureus were spa type t605 and carried a wide variety of virulence factors, including icaD, fib, fnbA, clfA, bap, clfB, icaA, see, and sed. The most common antimicrobial resistance gene was blaZ, associated with beta-lactam resistance, followed by aac6'aph2' and ant4, both linked to aminoglycoside resistance. The spa type t605 MSSA is endemic in São Paulo, Brazil, and is highly resistant to penicillin. The study found that basil and bergamot EOs were effective against S. aureus at 10³ CFU.mL⁻¹ , while clove, arrayan, and spearmint EOs showed strong antimicrobial action at 10⁷ CFU.mL⁻¹, with clove showing the most promising results. GC/MSD analyses revealed the principal constituents of these EOs: eugenol in clove (86.25%), limonene in arrayan (32.64%), and carvone in spearmint (63.21%). The study also used sub-minimum inhibitory concentrations (sub-MICs) to assess biofilm formation for the EOs of spearmint + arrayan, spearmint, arrayan, and clove. Results showed a reduction in biofilm formation; at 24 hours, the OD was 0.085, while at 48 hours, it reduced to 0.078. Further, OD decreased from 0.094 at 1/4 MIC to 0.069 at 1/16 MIC. Tested EOs showed cytotoxicity on Vero cells; clove EO had an IC₅₀ of 0.021. Despite promising antimicrobial results, cytotoxicity tests raised concerns about the safety of these EOs. The study contributes to a deeper understanding of the virulence, genomic variations, and antibiotic resistance of S. aureus. The study emphasizes the potential of EOs as natural alternatives to antibiotics for treating S. aureus in bovine mastitis but raises concerns about their cytotoxicity; further investigations are needed to optimize formulations and assess in vivo efficacy and safety.